HELLP syndrome preceded by intrahepatic cholestasis of pregnancy: one serious itch. (7th April 2014) - Jebbink, Jiska; Tabbers, Merit; Afink, Gijs; Beuers, Ulrich; Elferink, Ronald Oude; Ris-Stalpers, Carrie; van der Post, Joris
Abstract : We present four women with seven ongoing pregnancies. Five pregnancies were complicated by intrahepatic cholestasis of pregnancy (ICP) and severe haemolysis, elevated liver enzymes and low platelets (HELLP) syndrome with uncommon maternal morbidity. The combination of ICP and HELLP syndrome has not previously been reported. Awareness is warranted to accurately identify this combination of pregnancy-specific diseases with severe maternal morbidity.